Pemberdayaan Kopontren Makmur Bersama Melalui Pembuatan Sabun Cuci Piring (Silau) - Abd. Hadi; Manaruz Zaman Alkhoiri; Miftahul Barri; Moh. Firman Adi Purnama; Farikhatul Ilmiyah; Ilmina Daroja; Masfufah Nurrokhmah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Makmur Bersama (MBS) is a copontren of the Darussalam Islamic boarding school, Dungmas, Kedungrejo, Sumberejo, Bojonegoro, the products sold are basic food materials, especially LPG and refilled water, thus the problem is the lack of knowledge for making their own products and the absence of training on knowledge skills that make opportunities for the empowerment of Islamic boarding school cooperatives. justification for the solution to the problem is to increase the knowledge and skills of employees in processing dish soap. efforts to increase the additional income of Islamic boarding school cooperatives, assist Islamic boarding schools cooperatives to promote employee welfare and socialize the results of the product through nearby shops and online. Furthermore, the method of implementing the service is a survey, monitoring and evaluation training.